2007
DOI: 10.1016/j.jmb.2007.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Multidrug Binding Protein TtgR in Complex with Antibiotics and Plant Antimicrobials

Abstract: Antibiotic resistance is a widely spread phenomenon. One major mechanism that underlies antibiotic resistance in bacteria is the active extrusion of toxic compounds through the membrane-bound efflux pumps that are often regulated at the transcriptional level. TtgR represses the transcription of TtgABC, a key efflux pump in Pseudomonas putida, which is highly resistant to antibiotics, solvents and toxic plant secondary products. Previously we showed that TtgR is the only reported repressor that binds to differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
180
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(187 citation statements)
references
References 31 publications
(58 reference statements)
6
180
1
Order By: Relevance
“…This was clearly demonstrated by the structures of the QacR 18,26 and Rv3066 14 regulators. A similar characteristic for the TetR-family regulators that recognize negatively charged antimicrobials has also been observed with TtgR 27 and CmeR. 28 In this case, positively charged histidines or lysines within the ligand-binding pockets are critical for the binding.…”
Section: Discussionmentioning
confidence: 61%
“…This was clearly demonstrated by the structures of the QacR 18,26 and Rv3066 14 regulators. A similar characteristic for the TetR-family regulators that recognize negatively charged antimicrobials has also been observed with TtgR 27 and CmeR. 28 In this case, positively charged histidines or lysines within the ligand-binding pockets are critical for the binding.…”
Section: Discussionmentioning
confidence: 61%
“…In this study, we identified five substrates of the RamR protein, including berberine, crystal violet, dequalinium, ethidium bromide and rhodamine 6G. Similar approaches in crystallizing the TetR family regulators with multiple drugs have been also reported in QacR 20 , TtgR 21 ARTICLE six amino acid substitutions in RamR that are related to bacterial drug resistance, including T18P, R46N, R46P, Y59H, M84I and E160D 15,17,23 . As shown in Supplementary Fig.…”
Section: Discussionmentioning
confidence: 62%
“…It was originally reported that all the ligands bind to QacR with a 1:2 stoichiometry (one ligand per QacR dimer), 20 whereas either 1:2 or 1:1 stoichiometry has been observed for RamR. Similar observations were reported in TtgR 21 . All the drugs studied, except dequalinium, were found completely buried in the RamR-binding pocket.…”
Section: Structure Of the Ramr Proteinmentioning
confidence: 57%
“…It is intriguing that the multidrug binding protein TtgR seems to utilize a different mechanism to recognize negatively charged antibiotics and plant antimicrobials. 21 The hydrophobic environment is provided in the ligand binding pocket at the C-terminal regulatory domain. In addition, a positively charged histidine and a polar asparagine are also found to involve in the binding.…”
Section: Discussionmentioning
confidence: 99%